#### Answer

$-\frac{1}{2}$

#### Work Step by Step

$\frac{3(-2)^{2} - 5}{-14}$ = $\frac{3(4) - 5}{-14}$ = $\frac{12 - 5}{-14}$ = $\frac{7}{-14}$ = $-\frac{1}{2}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$-\frac{1}{2}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.